Comparison of Compressive Strength and Wood Powder Absorption and Coffee Grade Aggregate With Uniform Grade - Fahrizal Zulkarnain; Irma Dewi; Feri Iman Hasibuan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In Indonesia, there are many industrial wood processing factories that have a lot of waste or sawdust that has not been utilized. One solution to the utilization of sawdust waste is to use it as a construction material. Wood sawdust is waste obtained from the results of wood craftsmen who use machines or manually. Utilization of wood waste is now used as material for making cabinets and gardening. One solution to the utilization of sawdust waste is to use it as a construction building material. Food industry waste can cause problems in handling because it contains carbohydrates, proteins, fats, mineral salts and also chemical residues used in processing and cleaning. Waste that is increasing and piling up will smell and become a source of microbial development which in the end will also cause various kinds of diseases, so that food industry waste needs good handling. Coffee grounds are also food industry waste produced from processing coffee beans. As with other food industry waste, coffee grounds waste has the potential to be used as a substitute material for cement.